Front Cover: Transition‐Metal Carbonyl Complexes and Electron‐Donating Properties of N‐Heterocyclic‐Carbene–Phosphinidene Adducts (Eur. J. Inorg. Chem. 23/2016). Issue 23 (August 2016) - Bockfeld, Dirk; Doddi, Adinarayana; Jones, Peter G.; Tamm, Matthias
Abstract : The cover picture shows the structure of an N‐heterocyclic‐carbene–phosphinidene–tungsten complex, which was used, together with other carbonyl complexes of tungsten, molybdenum, and rhodium, to establish by IR spectroscopy that NHC–phosphinidenes represent a new class of strongly electron‐donating phosphorus ligands. In the background is an image of the Brunswick Lion, which refers to our home town, the "Lion City", and to our university. Details are discussed in the article by M. Tamm et al. onp. 3704 ff . For more on the story behind the cover research, see theCover Profile .